Democracy as Political Jihad: Evaluating Yusuf Qaradhawi's Vision and its Application in Indonesia - Ramadan, Risky Aulya; Muzammil, Shofiyullah (Islamic Thought Review, 2024)
This article examines the influence of Western secular thought on Islamic civilization, focusing on its repercussions within the political domain. The dominance of secular politics, which often conflicts with Islamic values, poses a significant challenge to Islamic governance principles. In response to this ideological shift, Yusuf Qaradhawi has called for a political reformation grounded in Islamic teachings, framing this transformative effort as a form of jihad. To investigate this perspective, the study employs qualitative research methods, specifically library-based research, and document analysis. Primary data is sourced from Yusuf Qaradhawi's own writings, while secondary data includes a range of books, scholarly journals, bulletins, and encyclopedias pertinent to the topic. The analysis reveals that the core principles of democracy—such as the right of citizens to elect their leaders freely—are compatible with Islamic values. However, the study also identifies notable deviations from these democratic ideals in practice. In the context of Indonesia, where Islamic values have been incorporated into the democratic framework, discrepancies between theoretical principles and actual political practices remain significant. This paper not only highlights the alignment between Islamic principles and democratic values but also critically assesses the challenges and inconsistencies faced in their implementation.